2017
DOI: 10.19082/3823
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in patients with chronic suppurative otitis media: Is there a significant correlation?

Abstract: IntroductionHearing loss as a sequel of chronic suppurative otitis media (CSOM) is often conductive, but recent studies have found an additional sensorineural component in these patients, thus demonstrating inner ear damage. The aim of the study was to determine the association between CSOM and sensorineural hearing loss (SNHL) and to assess the influence of patient’s age, duration of disease, and presence of cholesteatoma and ossicular erosion on the degree of SNHL.MethodsIn a retrospective study, the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 20 publications
6
49
0
2
Order By: Relevance
“…However, they did not identify any correlation between the patient's age or duration of disease and the degree of SNHL. Amali et al [4] report that a statistically significant difference in mean BCT was obtained on PTA between normal and diseased ears at all frequencies. The authors found that there was a significant correlation between age and SNHL, but that the duration of the disease did not have a significant effect on SNHL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, they did not identify any correlation between the patient's age or duration of disease and the degree of SNHL. Amali et al [4] report that a statistically significant difference in mean BCT was obtained on PTA between normal and diseased ears at all frequencies. The authors found that there was a significant correlation between age and SNHL, but that the duration of the disease did not have a significant effect on SNHL.…”
Section: Discussionmentioning
confidence: 96%
“…[1] Whilst COM is usually associated with conductive hearing loss, it may also cause sensorineural hearing loss (SNHL). [2][3][4][5] Conductive hearing loss due to COM is extensively discussed in the literature, but the relationship between SNHL and COM remains controversial. [1] Inflammatory mediators and lytic enzymes produced by the reactive middle ear epithelium are thought to be the main reason for SNHL in cases of COM.…”
Section: Introductionmentioning
confidence: 99%
“…Amali A et al [9] found that older patients were more vulnerable to the effects of middle ear inflammation on cochlear function, and this vulnerability could lead to intense hearing impairment due to aging. Age-related hearing loss (ARHL) or presbycusis is one of the most common disabilities in elderly people, which affects approximately 27.6% of individuals between 65 to 79 years and 36.5% of those aged 80 and older.…”
Section: Discussionmentioning
confidence: 99%
“…With this background present study was planned to study of pattern of hearing loss in CSOM in Indian Population. Hearing loss as a sequel of chronic suppurative otitis media (CSOM) is often conductive, but recent studies have found an additional sensorineural component in these patients, thus demonstrating inner ear damage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic suppurative otitis media (CSOM) is the chronic inflammation of the middle ear fossa with discharge through a perforated tympanic membrane [1]. Hearing loss is a public health problem in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%